2022
DOI: 10.1128/spectrum.00964-22
|View full text |Cite
|
Sign up to set email alerts
|

Contaminated Incubators: Source of a Multispecies Enterobacter Outbreak of Neonatal Sepsis

Abstract: Neonatal incubators in the NICU can be an important reservoir of pathogens responsible for life-threatening outbreaks in neonatal patients. Traditional disinfection with antiseptics is not sufficient to eradicate the microorganisms that can persist for long periods in the different reservoirs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…We cannot exclude that these bacteria were present in another site of the incubator that has not been sampled and grow up with the moistening and heat of the incubator. This hypothesis is in agreement with the work of Hernandez-Alonso et al who found that the recovery of Enterobacter from incubators after disinfection was facilitated after the incubator was running on, probably because in this condition temperature and humidity are optimal for bacterial regrowth [28]. Furthermore, the early contamination of incubators can come from caregivers and parents.…”
Section: Discussionsupporting
confidence: 91%
“…We cannot exclude that these bacteria were present in another site of the incubator that has not been sampled and grow up with the moistening and heat of the incubator. This hypothesis is in agreement with the work of Hernandez-Alonso et al who found that the recovery of Enterobacter from incubators after disinfection was facilitated after the incubator was running on, probably because in this condition temperature and humidity are optimal for bacterial regrowth [28]. Furthermore, the early contamination of incubators can come from caregivers and parents.…”
Section: Discussionsupporting
confidence: 91%
“…Currently, there are 56 species within the genus Enterobacter, 22 of which are published with accepted names [List of Prokaryotic Names with Standing in Nomenclature (accessed: 7 June 2023); https://lpsn.dsmz.de/genus/ Enterobacter] [47]. Although not all species are pathogenic, some have emerged as important nosocomial pathogens and are generally referred to as the Enterobacter cloacae complex [48][49][50][51]. The Enterobacter T6SS has been investigated in E. cloacae type strain ATCC 13047, which possesses two T6SS clusters (termed T6SS-1 and T6SS-2) utilized for gut colonization, bacterial competition, biofilm formation and epithelial cell adherence [40].…”
mentioning
confidence: 99%